Social Intellisense: A Task-Embedded Interface to Folksonomies - Counts, Scott; Fisher, Kristie; Hoff, Aaron (Proceedings of the Fourth International Conference on Weblogs and Social Media, 2010)
We present an application for accessing and creating socially constructed sets of information. Users store and retrieve information, such as bits of text, through the use of “keys” consisting of node names strung together using periods (e.g., “conferences.icwsm.dates”) that point to user-added content (“May 23-26, 2010”). Furthermore, nodes can point to services on the web (e.g., “facebook.me.status” retrieves the user‟s current Facebook status). In short, Social Intellisense is a user interface mechanism for folksonomies that allows users to collaboratively “remap” web and user-added content via strings of their own creation. A study with our Social Intellisense-enabled email client showed that the paradigm is comparable or preferable to traditional web browser methods for retrieving certain information online. Issues and potential solutions to mismatches between a user‟s task at hand and collaboratively organized information are discussed.